2008
DOI: 10.1105/tpc.108.060699
|View full text |Cite
|
Sign up to set email alerts
|

ArabidopsisPUB22 and PUB23 Are Homologous U-Box E3 Ubiquitin Ligases That Play Combinatory Roles in Response to Drought Stress

Abstract: Ubiquitination is involved in diverse cellular processes in higher plants. In this report, we describe Arabidopsis thaliana PUB22 and PUB23, two homologous U-box-containing E3 ubiquitin (Ub) ligases. The PUB22 and PUB23 genes were rapidly and coordinately induced by abiotic stresses but not by abscisic acid. PUB22-and PUB23-overexpressing transgenic plants were hypersensitive to drought stress. By contrast, loss-of-function pub22 and pub23 mutant plants were significantly more drought-tolerant, and a pub22 pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
184
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(199 citation statements)
references
References 39 publications
8
184
1
1
Order By: Relevance
“…25 Indeed, AtPUB22/23 overexpression caused hypersensitivity to drought stress, while their loss of function resulted in drought tolerance. 21,22 This is somewhat paradoxical since the stress-induced expression of both ligases suggested that they are needed by plant cells to counteract the negative impact of the stress. The AtPUB22/23 overexpression studies did reveal two potentially beneficial traits for plants subjected to water stress: increased root elongation, which increases a plants' ability to maintain water uptake, and accelerated flowering that secures the production of progeny under adverse conditions.…”
Section: The 26sp and Stress Responsesmentioning
confidence: 94%
See 1 more Smart Citation
“…25 Indeed, AtPUB22/23 overexpression caused hypersensitivity to drought stress, while their loss of function resulted in drought tolerance. 21,22 This is somewhat paradoxical since the stress-induced expression of both ligases suggested that they are needed by plant cells to counteract the negative impact of the stress. The AtPUB22/23 overexpression studies did reveal two potentially beneficial traits for plants subjected to water stress: increased root elongation, which increases a plants' ability to maintain water uptake, and accelerated flowering that secures the production of progeny under adverse conditions.…”
Section: The 26sp and Stress Responsesmentioning
confidence: 94%
“…[21][22][23] The hot pepper (Capsicum annuum L.) U-box protein 1 (CaPUB1) and its Arabidopsis homologues AtPUB22 and AtPUB23 are Ub ligases, and the corresponding genes are rapidly induced by abiotic stresses such as desiccation, cold and mechanical wounding. 21,22 Both the hot pepper and Arabidopsis PUBs seem to interfere with 26SP function by ubiquitinating specific subunits of the RP lid subcomplex. CaPUB1 ubiquitinates RPN6, and because the RPN6 level was reduced in CaPUB1 overexpressing plants, it has been suggested that the ubiquitination leads to the destabilization of this RP subunit.…”
Section: The 26sp and Stress Responsesmentioning
confidence: 99%
“…For example, in Arabidopsis (Arabidopsis thaliana), the 26S proteasome-mediated degradation of DEHYDRATION-RESPONSIVE ELEMENT BINDING PROTEIN2A (DREB2A) is promoted by the negative regulators of drought-responsive gene expression DREB2A-INTERACTING PROTEIN1 (DRIP1) and DRIP2 (Qin et al, 2008). The Arabidopsis U-box-type E3 ubiquitin ligases PLANT U-BOX22 (PUB22) and PUB23 jointly regulate a drought signaling pathway by ubiquitinating cytosolic REGULATORY PARTICLE NON-ATPASE12A (Cho et al, 2008) and drought stress-induced Rma1H1, which is a hot pepper (Capsicum annuum) homolog of a human RING (Really Interesting New Gene) membraneanchor1 E3 ubiquitin ligase that regulates aquaporin levels via ubiquitination (Lee et al, 2009a). Triticum durum RING Finger1 (TdRF1) may act as a nuclear E3 ligase in durum wheat, where it regulates the abiotic stress response by promoting degradation of the WHEAT BEL1-TYPE HOMEODOMAIN1 (WBLH1) transcription factor through the 26S proteasome in vivo (Guerra et al, 2012).…”
mentioning
confidence: 99%
“…Arabidopsis AtPUB22, AtPUB23 and AtPUB24 redundantly and negatively regulate PTI 10 . In addition, AtPUB22 and AtPUB23 also function as negative regulators in the water-stress response 36 . Recently, Exo70B2, a component of the exocytic machinery, was identified as a substrate for AtPUB22 (ref.…”
Section: Wt 1mentioning
confidence: 99%